THE EFFECT OF SOME OF COCONUT WATER CONCENTRATION IN ARTIFICIAL MEDIA TO CHRYSANTHEMUM GROWTH (Dendranthema grandiflora) BY IN VITRO - Nurur Rahmy; Zairin Thomy; Yunita Yunita; Essy Harnelly (Jurnal Natural, 2019)
Artificial medium for in vitro culture is an alternative media to subtitute Murashige and Skoog (MS). Growmore added with organic substances as coconut water can be used as artificial medium. Coconut water can affect plant growth, so the research is to investigate the influence of coconut water in different concentration to chrysanth’s (Dendranthema grandiflora) growth should be done. The research was conducted in Laboratory of Molecular and Cell Biology, Department of Biology, Faculty of Mathematics and Natural Sciences, Syiah Kuala University Darussalam, Banda Aceh, from April until July 2013. The research was designed by using Randomized Block Design with sub sampling. Media act as group, while coconut water concentration as treatment. Observation was started from growing time up to a month after planting. The result showed that there was no significant different between using MS and artificial medium with different coconut water concentration to initiate shootlet.